Management of Pregnancy with Covid-19: A Systematic Review - Lutfiana Puspita Sari; Rendi Editya Darmawan; Emy Suryani; Sofia Sagita (Poltekkes Kemenkes Semarang, 2022)
Backgrounds: COVID-19 is a new virus that comes since 2019, and attacks the respiratory system. Pregnant women are at high risk for adverse effects from Covid-19 infection, because of the adaptive cardiopulmonary changes during pregnancy. During the COVID-19 pandemic, physiological changes during pregnancy are feared to increased maternal morbidity and mortality from COVID-19 infection. Safe and effective antenatal care is carried out through special management during the COVID-19 pandemic.Purpose: aim of study is to analyze symptoms, management of pregnancy, childbirth, neonatal, pharmacological therapy and COVID-19 vaccination in pregnant women.Methods: this research used systematic review method. The samples was obtained from ScienceDirect, Wiley and Pubmed database. The keyword are pregnant women, Covid-19, management pregnancy with Covid-19.Results: 10 original research articles was find and accordance with criteria. Management of COVID-19 pregnancy was regulated to reduce exposure the virus in mother and child population. Multidisciplinary health workers were needed to oversee the continuous care of mothers. COVID-19 vaccine in pregnant women was considered safe for mother and fetus.Conclusion: management or guidelines of COVID-19’s pregnancy was carried out continuously and comprehensively to reduce the high rate of morbidity and mortality. COVID – 19 vaccination was attempted as a preventive and protective measure for pregnant women.